Genetic and morphometric differentiation between island and mainland southern elephant seal populations - Hoelzel,Rus A. (2001)
We compare genetic (both nuclear and mitochondrial) and morphometric measures between two putative populations of southern elephant seal (Mirounga leonina), and interpret the results in the context of data from mark-recapture and satellite-telemetric studies. One population is on the Argentine mainland, while the other is 2400 km away on South Georgia island. We found pronounced differentiation at the mitochondrial DNA (mtDNA) control region that was distinct from the pattern of variation seen among island rookeries. Some morphometric characters and seven out of ten nuclear-DNA markers also showed differentiation between the island and mainland sites. Diversity at nuclear markers was high in both populations but mtDNA diversity was low in the mainland population, suggesting a founder event and little subsequent immigration of females. Morphological differences may suggest different selective environments at the two sites.